Optimizing Students' HOTS Skills through AI and IoT Integration in Digital Technology Learning - Farizi, Zakaria Al; Nurfadilah, Nurfadilah; Arifin, Anggun Syafira; Fitriani, Nadya (FKIP Universitas Lampung, 2024)
Higher-order thinking skills (HOTS) are essential for students to face increasingly complex global challenges. However, results from the Programme for International Student Assessment (PISA) indicate that these skills among Indonesian students remain low. This study aims to address this limitation by integrating Artificial Intelligence (AI) and Internet of Things (IoT) technologies into learning, specifically to enhance students' HOTS within the framework of the Kurikulum Merdeka. This research employs a quasi-experimental method with a one-group pretest-posttest design, involving three schools in East Nusa Tenggara as the sample. Data on students' HOTS were collected before and after the AI and IoT-based learning intervention and analyzed using paired sample T-tests and N-Gain to assess the significance and effectiveness of the improvement. The results show a significant increase in students' HOTS scores across all three schools, with p < 0.001 in paired sample T-tests and an average N-Gain score in the medium category. These findings suggest that AI and IoT-based learning can improve students' critical and analytical thinking skills. Implementing technology within the Kurikulum Merdeka offers relevant and promising benefits in preparing students to face future knowledge dynamics. This study contributes to the literature on technology-based education in Indonesia, with the hope that broader technology integration will accelerate the enhancement of national education quality. Keywords: higher-order thinking skills, artificial intelligence, internet of things, kurikulum merdeka, technology-based learning.DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1719-1737